Two-dimensional CsxRb1-xPbBr3 single-crystal nanosheet and preparation method thereof
By employing multi-parameter synergistic control in the chemical vapor deposition process, the problems of compositional deviation and lattice stress in CsxRb1-xPbBr3 single-crystal nanosheets were solved, enabling the preparation of high-quality, fully tunable two-dimensional CsxRb1-xPbBr3 single-crystal nanosheets with continuous adjustment of band gap and emission wavelength.
Patent Information
- Application Number
- CN202511760469.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-11-27
- Publication Date
- 2026-02-03
AI Technical Summary
Existing technologies struggle to achieve the controllable synthesis of high-quality, fully tunable two-dimensional CsxRb1-xPbBr3 single-crystal nanosheets, especially as the problems of lattice stress and compositional deviation caused by the ionic radius mismatch and volatility difference between Cs+ and Rb+ have not been effectively solved.
By using multi-parameter synergistic control of the chemical vapor deposition process, including precise weighing of precursor powder, grinding, low-pressure environment (10-30 Torr), and programmed temperature control, uniform doping of CsBr and RbBr and release of lattice stress are ensured, thereby achieving high crystallinity and compositional tunability of CsxRb1-xPbBr3 single-crystal nanosheets.
Two-dimensional CsxRb1-xPbBr3 single-crystal nanosheets with continuously tunable band gaps in the blue to green light range were successfully synthesized. The emission wavelength and photoelectric response performance of the material were precisely controlled, and the crystal quality and compositional uniformity were guaranteed.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This invention relates to the field of two-dimensional alloy material preparation technology, specifically a two-dimensional Cs x Rb 1-x PbBr3 single-crystal nanosheets and their preparation method. Background Technology
[0002] Two-dimensional all-inorganic perovskites (such as CsPbBr3) have attracted much attention in the field of nano-optoelectronic devices due to their excellent optoelectronic properties and higher environmental stability compared to three-dimensional structures. This paper discusses the construction of CsPbBr3 through A-site cation alloying. x Rb 1-x The PbBr3 system is considered an ideal approach to achieving continuous and precise bandgap tuning from blue to green light. Despite the immense potential of this material system, achieving high-quality, fully tunable two-dimensional Cs remains a challenge. x Rb 1-x The controllable synthesis of PbBr3 single-crystal nanosheets remains an unsolved problem in this field.
[0003] Existing research clearly reveals the inherent challenges in synthesizing such alloys. For example, Professor Zhang Long's research group at the Shanghai Institute of Optics and Fine Mechanics, Chinese Academy of Sciences, previously reported a three-dimensional Cs... x Rb 1-x Synthesis of PbBr3 micron-sized cubic lasing. While this work successfully achieved the alloying of Cs and Rb and explored its application potential in microcavity lasers, the research results show that the obtained three-dimensional alloy crystals suffer from problems such as insufficient crystallinity and poor stability. This example profoundly reflects that regardless of the synthesis route used, the synthesis of PbBr3... + With Rb + Significant ionic radius mismatch (approximately 0.19 Å) and differences in precursor properties are common bottlenecks restricting the formation of high-quality Cs-Rb perovskite alloys. These factors easily introduce stress into the lattice, leading to defect formation and structural instability.
[0004] Chemical vapor deposition (CVD) holds promise for obtaining higher quality crystals, but in Cs... x Rb 1-x There are two key technical challenges in the application of the PbBr3 system: First, the volatility of CsBr and RbBr differs by orders of magnitude (the volatilization temperature of CsBr is significantly higher than that of RbBr). In multi-source co-evaporation processes, simple mixing and heating can easily lead to preferential and excessive volatilization of the more volatile RbBr, causing the gas phase composition to deviate significantly from the designed ratio and resulting in macroscopic phase separation; Second, Cs + With Rb +An ionic radius mismatch of approximately 0.19 Å introduces significant stress into the lattice. If the deposition kinetics are mismatched, this stress can hinder the formation of long-range ordered single crystals and instead promote defect formation or amorphization. Therefore, it is crucial to develop a method that overcomes these limitations and achieves precisely controllable composition and high crystallinity in two-dimensional Cs. x Rb 1-x A universal synthesis method for PbBr3 single-crystal nanosheets is crucial for promoting the practical application of this material system in the field of integrated optoelectronics. Summary of the Invention
[0005] The purpose of this invention is to provide a two-dimensional Cs x Rb 1-x PbBr3 single-crystal nanosheets and their preparation method: This preparation method, through multi-parameter synergistic control of the chemical vapor deposition process, solves the key technical bottleneck in the Cs-Rb perovskite alloying process, and forms two-dimensional CsBr3 single-crystal nanosheets with high crystallinity. x Rb 1-x PbBr3 single-crystal nanosheets enabled continuous and controllable adjustment of the material's emission wavelength and photoelectric response within the blue to green light range.
[0006] This invention is implemented as follows: This invention provides a two-dimensional Cs with continuously adjustable bandgap. x Rb 1-x PbBr3 single-crystal nanosheets have the general chemical formula Cs x Rb 1-x PbBr3, where x is continuously adjustable in the range of 0 to 1 (0 ≤ x ≤ 1). Two-dimensional Cs x Rb 1-x PbBr3 single-crystal nanosheets have regular square or rectangular planar morphology, with lateral dimensions of tens of micrometers and characteristic thicknesses of 5-10 nanometers.
[0007] The present invention also provides the above-mentioned two-dimensional Cs x Rb 1-x A method for preparing PbBr3 single-crystal nanosheets. The method first involves accurately weighing CsBr, RbBr, and PbBr2 powders according to the target stoichiometric ratio, thoroughly mixing and grinding them to obtain precursor powder. Subsequently, under carrier gas and negative pressure conditions, the precursor powder is heated to the evaporation temperature T1 through programmed temperature rise, allowing it to fully vaporize and be transported to a mica substrate region at temperature T2 under the action of the carrier gas. Finally, high-quality two-dimensional CsBr3 nanosheets are obtained through vapor deposition. x Rb 1-x PbBr3 single-crystal nanosheets.
[0008] In Cs x Rb 1-xIn the synthesis of PbBr3 alloy systems, achieving full-component, uniform doping of A-site Cs / Rb cations is the primary technical bottleneck. This mainly faces two major challenges: first, the difference in volatility characteristics between Cs and Rb precursors easily leads to deviations in the gas phase composition from the macroscopic phase; second, lattice stress caused by ion radius mismatch hinders the formation of long-range ordered single crystals. To address this challenge, the process of this invention employs two key steps: first, the grinding and polishing treatment of the precursor aims to eliminate compositional inhomogeneity caused by differences in raw material properties at the source; second, the precise control of the system gas pressure within a specific low-pressure range of 10-30 Torr is crucial for achieving high-quality Cs doping. x Rb 1-x PbBr3 alloy nanosheets are crucial. This low-pressure condition achieves three core effects by significantly reducing the mean free path and collision frequency of gas phase molecules: First, it weakens the "preferential transport" effect of RbBr vapor caused by differences in mass and diffusion coefficients, forcing Cs and Rb vapors to be transported to the deposition region by the carrier gas at a more coordinated rate, thus ensuring the spatiotemporal consistency of gas phase components when arriving at the growth front from a kinetic perspective; Second, it greatly suppresses the probability of homogeneous nucleation in the gas phase, forcing the nucleation process to be confined to the substrate surface, which creates a prerequisite for two-dimensional layered epitaxial growth; Third, it lowers the migration barrier of adsorbed atoms on the substrate surface, promoting the uniform arrangement and stress release of Cs and Rb atoms at lattice sites.
[0009] In this invention, the evaporation temperature T1, deposition temperature T2, distance between the substrate and the T1 temperature zone, system pressure, and carrier gas flow rate are controlled in a coordinated manner to solve the co-evaporation problem caused by the difference in volatility between CsBr and RbBr and the co-evaporation of CsBr. + With Rb + The lattice stress problem caused by ionic radius mismatch, thus realizing Cs x Rb 1-x Atomic-level homogeneous alloying of PbBr3 across the entire composition range.
[0010] Preferably, x = 0.8~1, and the temperature of T1 is 470~500℃; x = 0.5~0.8, and the temperature of T1 is 420~470℃; x = 0.3~0.5, and the temperature of T1 is 380~420℃; x = 0~0.3, and the temperature of T1 is 350~380℃.
[0011] Preferably, the flow rate of the carrier gas is 30~100 sccm.
[0012] Preferably, in T2, x = 0.8~1, and the temperature of T2 is 315℃~325℃; x = 0.5~0.8, and the temperature of T2 is 275~315℃; x = 0.3~0.5, and the temperature of T2 is 245~275℃; x = 0~0.3, and the temperature of T2 is 215~245℃.
[0013] Preferably, the distance between the substrate and the T1 temperature zone is 1-2 cm. In this invention, the substrate is mica; preferably, the negative pressure is 10-30 Torr. Preferably, the deposition time is 15-120 min.
[0014] This invention provides a band-tunable all-inorganic two-dimensional Cs x Rb 1-x PbBr3 single-crystal nanosheets and their preparation method are presented. The process is simple, controllable, reproducible, and easily scalable. For the first time, two-dimensional Cs nanosheets were successfully synthesized in the complete range of 0 ≤ x ≤ 1 via a one-step vapor deposition method. x Rb 1-x PbBr3 alloy nanosheets. The band gap and emission wavelength of the material can be continuously and monotonically linearly tuned between 447 nm (blue light, RbPbBr3) and 525 nm (green light, CsPbBr3), providing an unprecedented material platform for designing high-performance optoelectronic devices with specific wavelengths. Attached Figure Description
[0015] Figure 1 This is a schematic diagram of the chemical vapor deposition apparatus used in the embodiments of the present invention.
[0016] Figure 2 These are test results of the two-dimensional CsPbBr3 single-crystal nanosheets prepared in Example 1 of this invention; wherein, a is an optical image of the two-dimensional CsPbBr3 single-crystal nanosheets; b is an EDS energy spectrum of the two-dimensional CsPbBr3 single-crystal nanosheets; c is a photoluminescence spectrum of the two-dimensional CsPbBr3 single-crystal nanosheets; and d is an X-ray diffraction pattern of the two-dimensional CsPbBr3 single-crystal nanosheets.
[0017] Figure 3 The two-dimensional Cs prepared in Example 2 of this invention 0.45 Rb 0.55 The test results of PbBr3 single-crystal nanosheets are shown in the figure; where a is a two-dimensional Cs 0.45 Rb 0.55 Optical image of PbBr3 single-crystal nanosheets; b is two-dimensional Cs 0.45 Rb 0.55 AFM analysis of PbBr3 single-crystal nanosheets; c is two-dimensional Cs 0.45 Rb 0.55 HRTEM image of PbBr3 single-crystal nanosheets; d is two-dimensional Cs 0.45 Rb 0.55Selected area electron diffraction pattern of PbBr3 single-crystal nanosheets.
[0018] Figure 4 The two-dimensional Cs prepared in Example 2 of this invention 0.45 Rb 0.55 EDS spectrum, XRD pattern and PL spectrum of PbBr3 single crystal nanosheets; where a is the EDS spectrum, b is the XRD pattern and c is the PL spectrum.
[0019] Figure 5 The two-dimensional Cs prepared in Example 3 of this invention 0.31 Rb 0.69 The test results of PbBr3 single-crystal nanosheets are shown in the figure; where a is a two-dimensional Cs 0.31 Rb 0.69 Optical image of PbBr3 single-crystal nanosheets; b is two-dimensional Cs 0.31 Rb 0.69 EDS spectrum of PbBr3 single-crystal nanosheets; c is two-dimensional Cs 0.31 Rb 0.69 Photoluminescence spectrum of PbBr3 single-crystal nanosheets; d represents two-dimensional Cs 0.31 Rb 0.69 X-ray diffraction pattern of PbBr3 single-crystal nanosheets.
[0020] Figure 6 These are test results of the two-dimensional RbPbBr3 single-crystal nanosheets prepared in Example 4 of this invention; wherein, a is an optical image of the two-dimensional RbPbBr3 single-crystal nanosheets; b is an EDS energy spectrum of the two-dimensional RbPbBr3 single-crystal nanosheets; c is a photoluminescence spectrum of the two-dimensional RbPbBr3 single-crystal nanosheets; and d is an X-ray diffraction pattern of the two-dimensional RbPbBr3 single-crystal nanosheets.
[0021] Figure 7 These are optical images and photoluminescence spectra of the sample prepared in Comparative Example 1 of this invention; wherein, a is an optical image and b is a photoluminescence spectrum.
[0022] Figure 8 These are optical images and photoluminescence spectra of the sample prepared in Comparative Example 2 of this invention; wherein, a is an optical image and b is a photoluminescence spectrum. Detailed Implementation
[0023] The present invention will be further described in detail below with reference to the accompanying drawings and specific embodiments. These examples are provided to facilitate a more comprehensive understanding and reproduction of the present invention by those skilled in the art. It should be understood that these specific descriptions do not constitute a limitation on the scope of protection of the present invention, and the specific implementations covered by the present invention are not limited to any of the embodiments listed below.
[0024] Example 1: Preparation of two-dimensional CsPbBr3 single-crystal nanosheets.
[0025] Step (1): Preparation of precursor powder.
[0026] In this step, the precursor powder is synthesized using CsBr and PbBr2 (molar ratio 1:1) as starting materials. After grinding the two materials thoroughly, CsPbBr3 precursor powder is formed, and the CsPbBr3 precursor powder is placed in a porcelain boat.
[0027] Step (2): Preparation of CsPbBr3 single crystal nanosheets.
[0028] A schematic diagram of the chemical vapor deposition apparatus used in this experiment is shown below. Figure 1 The core component is a horizontal quartz tube with an inlet on the left and an outlet on the right. The heating zone of the quartz tube is divided into two temperature zones: an upstream high-temperature zone and a downstream low-temperature zone. The upstream high-temperature zone is used to place a ceramic boat loaded with precursor powder, and the downstream low-temperature zone is used to place a mica substrate. Carrier gas enters through the inlet. The precursor powder in the ceramic boat in the upstream high-temperature zone will form precursor vapor at high temperature. The carrier gas carries the precursor vapor to deposit on the substrate surface to form nanosheets. The specific operation of this step is as follows: The ceramic boat containing CsPbBr3 precursor powder is placed in the upstream high-temperature zone of the quartz tube, and the temperature of the high-temperature zone T1 is set to 350℃; while the fresh mica sheet, which serves as the deposition substrate, is placed downstream, about 2 cm from the center of the upstream high-temperature zone, and the temperature of the downstream low-temperature zone T2 where the mica sheet is located is 215℃. The entire growth process is carried out in a low-pressure environment (10 Torr) maintained by a vacuum pump, with an Ar gas flow rate of 30 sccm and a deposition time of 15 minutes.
[0029] After 15 minutes of vapor deposition, a structure like this was formed on the substrate. Figure 2 Image a shows a two-dimensional CsPbBr3 single-crystal nanosheet with a regular morphology. From... Figure 2 The optical microscope image in section a shows that the CsPbBr3 single-crystal nanosheets have a regular rectangular geometric morphology, a smooth and flat surface, a lateral dimension of approximately 20-40 μm, and sharp, clear edges, indicating that the sample has good crystallinity. The energy dispersive spectroscopy (EDS) spectrum of the two-dimensional CsPbBr3 single-crystal nanosheets is shown below. Figure 2 As shown in Figure b, the energy dispersive spectroscopy (EDS) clearly displays the characteristic peaks of Cs, Pb, and Br. Quantitative analysis yielded an atomic percentage of Cs:Pb:Br = 17.32:20.57:62.11, which highly agrees with the theoretical stoichiometric ratio of 1:1:3, indicating the successful preparation of CsPbBr3 single-crystal nanosheets. The PL spectrum of the two-dimensional CsPbBr3 single-crystal nanosheets is shown below. Figure 2As shown in Figure c, the sample exhibits a narrow half-maximum (HWHM) and symmetrical strong emission peak at 525 nm, which is attributed to band-edge luminescence of CsPbBr3. The accurate peak position and symmetrical peak shape demonstrate that the prepared nanosheets possess excellent crystal quality and optical properties. The XRD test results of the two-dimensional CsPbBr3 single-crystal nanosheets are shown below. Figure 2 As shown in Figure d, no impurity phase peaks appear in the XRD pattern, and the diffraction peaks are sharp. The XRD diffraction pattern is similar to the standard spectrum of monoclinic CsPbBr3. Figure 1 The presence of crystallinity indicates that the sample is a pure phase and has high crystallinity.
[0030] Example 2, Two-dimensional Cs 0.45 Rb 0.55 Preparation of PbBr3 single-crystal nanosheets.
[0031] Step (1): Preparation of precursor powder.
[0032] In this step, the precursor powder is synthesized using CsBr, RbBr, and PbBr2 as starting materials, with the molar ratio of the three precisely controlled at 0.45 : 0.55 : 1. After thorough grinding, CsBr is formed. 0.45 Rb 0.55 PbBr3 precursor powder, Cs 0.45 Rb 0.55 PbBr3 precursor powder was placed in a porcelain boat.
[0033] Step (2): Cs 0.45 Rb 0.55 Preparation of PbBr3 single-crystal nanosheets.
[0034] The difference between this step and step (2) in Example 1 is that the temperature T1 for the precursor powder to evaporate is 390°C, the temperature T2 for the mica substrate is 255°C, the mica sheet is placed approximately 1.5 cm downstream from the center of the high-temperature zone, the argon flow rate is 50 sccm, the pressure is maintained at 18 Torr, and the deposition time is maintained at 60 min. After deposition, two-dimensional Cs is obtained. 0.45 Rb 0.55 PbBr3 single-crystal nanosheets.
[0035] The obtained two-dimensional Cs 0.45 Rb 0.55 Performance tests were conducted on PbBr3 single-crystal nanosheets, and the results are as follows: Figure 3 As shown. Figure 3In the image, Figure a clearly shows its regular rectangular geometry, smooth surface, sharp edges, and uniform lateral dimensions of approximately 20 μm. Figure b is an AFM analysis image, further demonstrating that the nanosheet has a smooth surface and uniform thickness. Cross-sectional height measurements confirm that the nanosheet has a uniform thickness, with a characteristic thickness of approximately 7.8 nm. Figure 3 The high-resolution transmission electron microscope (HRTEM) image in Figure c shows atomically resolved lattice fringes, indicating that the nanosheet is a high-quality two-dimensional single-crystal structure. The measured interplanar spacings of (100) and (001) are 0.576 nm and 0.583 nm, respectively, both smaller than the corresponding values of pure phase CsPbBr3, directly confirming that Rb + Lattice shrinkage caused by doping. Furthermore, the corresponding selected area electron diffraction (SAED) ( Figure 3 The pattern shown in Figure d is a set of sharp and orderly diffraction spots, which proves its perfect single-crystal characteristics and good long-range order.
[0036] Two-dimensional Cs 0.45 Rb 0.55 The EDS spectrum, XRD pattern, and PL spectrum of PbBr3 single-crystal nanosheets are shown below. Figure 4 Figures a, b, and c are shown in the diagram. Figure a shows the detection of four elements: Cs, Rb, Pb, and Br. The calculated atomic percentages are approximately 10.17:12.30:19.38:58.16, which is consistent with the target stoichiometric ratio of Cs. 0.45 Rb 0.55 The PbBr3 match indicates that two-dimensional Cs were successfully prepared. 0.45 Rb 0.55 PbBr3 single-crystal nanosheets. From Figure 4 The X-ray diffraction pattern shows that its peak position is different from that of CsPbBr3 (see attached image). Figure 2 c) A systematic high-angle shift occurred, confirming the formation of a homogeneous alloy phase and the presence of Rb. + The shrinkage of the lattice constant caused by doping. Figure 4 The photoluminescence spectrum of the sample showed a strong, symmetrical emission peak with a narrow half-maximum width at 480 nm, exhibiting strong band-edge emission. Compared to CsPbBr3 (525 nm), this emission peak showed a significant blue shift, directly proving that the band gap was continuously controlled through A-site cation alloying. This result fully demonstrates that the process of this invention can effectively control the crystal structure and luminescence properties of two-dimensional perovskites through precise composition control.
[0037] Example 3, Two-dimensional Cs 0.31 Rb 0.69 Preparation of PbBr3 single-crystal nanosheets.
[0038] Step (1): Preparation of precursor powder.
[0039] In this step, the precursor powder is synthesized using CsBr, RbBr, and PbBr2 as starting materials, with the molar ratio of the three precisely controlled at 0.31 : 0.69 : 1. After thorough grinding, CsBr is formed. 0.31 Rb 0.69 PbBr3 precursor powder, Cs 0.31 Rb 0.69 PbBr3 precursor powder was placed in a porcelain boat.
[0040] Step (2): Cs 0.31 Rb 0.69 Preparation of PbBr3 single-crystal nanosheets.
[0041] The difference between this step and step (2) in Example 1 is that the temperature T1 for the precursor powder to evaporate is 385℃, the temperature T2 for the mica substrate is 250℃, the mica sheet is placed approximately 1.4 cm downstream from the center of the high-temperature zone, the argon flow rate is 70 sccm, the pressure is maintained at 23 Torr, and the deposition time is maintained at 70 min. After deposition, two-dimensional Cs is obtained. 0.31 Rb 0.69 PbBr3 single-crystal nanosheets.
[0042] The obtained two-dimensional Cs 0.31 Rb 0.69 Performance tests were conducted on PbBr3 single-crystal nanosheets, and the results are as follows: Figure 5 As shown. Figure 5 In Figure a, the optical microscopic image clearly shows the synthesized Cs. 0.31 Rb 0.69 PbBr3 single-crystal nanosheets possess properties similar to CsPbBr3 and Cs 0.45 Rb 0.55 The PbBr3-like regular rectangular morphology, with a smooth surface and clear edges, and uniform lateral dimensions distributed on the order of tens of micrometers, indicates that the method of the present invention has good universality for different A-site cation components, especially intermediate alloy components, and can guide crystals to achieve perfect two-dimensional epitaxial growth. Figure 5 b is the corresponding EDS spectrum, which clearly detects the presence of four elements: Cs, Rb, Pb, and Br. Their atomic percentages, calculated to be approximately 6.71:14.93:19.59:58.77, are consistent with the target stoichiometric ratio of Cs. 0.31 Rb 0.69 The high match with PbBr3 further confirms the precise controllability of the composition achieved by the method of this invention. Photoluminescence spectrum ( Figure 5c) Strong band-edge emission is exhibited at 472 nm, with a significant blue shift relative to CsPbBr3 and a narrowed full width at half maximum (FWHM). This directly confirms that the parameter-coordinated control method of this invention successfully achieved uniform alloying of Cs and Rb at the A site, resulting in Cs with high crystal quality and uniform composition. 0.31 Rb 0.69 PbBr3 alloy. X-ray diffraction pattern ( Figure 5 d) The diffraction peaks show a shift in position compared to CsPbBr3, confirming the formation of a homogeneous alloy phase and demonstrating the pure phase characteristics and high crystallinity of the product.
[0043] Example 4: Preparation of two-dimensional RbPbBr3 single-crystal nanosheets.
[0044] Step (1): Preparation of precursor powder.
[0045] In this step, the precursor powder is synthesized using RbBr and PbBr2 (molar ratio 1:1) as starting materials. After grinding the two materials thoroughly, RbPbBr3 precursor powder is formed and placed in a porcelain boat.
[0046] Step (2): Preparation of RbPbBr3 single crystal nanosheets.
[0047] The difference between this step and step (2) in Example 1 is that the temperature T1 for the precursor powder to evaporate is 500℃, the temperature T2 for the mica substrate is 325℃, the mica sheet is placed downstream about 1 cm from the center of the upstream high-temperature zone, the argon flow rate is 100 sccm, the pressure is maintained at 30 Torr, and the deposition time is maintained at 120 min. After deposition, two-dimensional RbPbBr3 single-crystal nanosheets are obtained.
[0048] The performance of the obtained two-dimensional RbPbBr3 single-crystal nanosheets was tested, and the results are as follows: Figure 6 As shown. Figure 6 In Figure a, the optical microscope image shows that it has a regular rectangular geometry similar to CsPbBr3, with a smooth surface and clear edges. Figure 6 b is the corresponding EDS spectrum, which detects the presence of Rb, Pb, and Br elements, with an atomic percentage of approximately 20.56:22.07:57.37, which is highly consistent with the theoretical stoichiometry of RbPbBr3. Photoluminescence spectrum ( Figure 6 c) A strong blue emission peak with a narrow half-maximum and symmetrical shape is observed at 447 nm, which is the band-edge emission of RbPbBr3. This peak differs from the green emission of CsPbBr3 (525 nm) and CsPbBr3. 0.45 Rb 0.55 Blue-green light emission of PbBr3 (480 nm) and Cs 0.31Rb 0.69 The blue light emission (472 nm) of PbBr3 together constitutes a continuously tunable light-emitting system from blue to green light, fully demonstrating the ability of this invention to achieve precise control of crystal structure and optical properties across the entire composition range. Figure 6 d is the XRD pattern. All diffraction peaks perfectly match the standard card of monoclinic RbPbBr3, and there are no impurity peaks, which confirms the pure phase and high crystallinity of the product.
[0049] Comparative Example 1 The process steps in this comparative example are largely the same as in Example 2, except that the precursor powders are simply mixed together without grinding. All other steps are the same. The optical images and PL spectra of the obtained samples are as follows: Figure 7 As shown. By Figure 7 As can be seen from a, the sample morphology is irregular, indicating preparation failure. Furthermore, the sample's PL spectrum (...) Figure 7 (b) A distinct double-peak emission was observed at 494 nm and 511 nm, which is a typical characteristic of phase separation. This result demonstrates that without sufficient grinding, the difference in physical properties between the Cs and Rb precursors cannot be overcome, and the high-quality, homogeneous single alloy phase described in this invention cannot be obtained.
[0050] Comparative Example 2 The process steps in this comparative example are largely the same as in Example 3, except that atmospheric pressure (760 Torr) was used for preparation. All other steps are the same. The optical images and PL spectra of the obtained samples are as follows: Figure 8 As shown. By Figure 8 As can be seen from a, the prepared material is dense but irregular in shape, indicating a preparation failure. The PL spectrum of the sample ( Figure 8 b) A distinct double peak appears near 482 nm and 464 nm. This result demonstrates that, under normal pressure conditions, the transport differentiation and surface migration barriers between the Cs and Rb precursors cannot be overcome, making it impossible to obtain the homogeneous, highly crystalline single alloy phase described in this invention. Instead, it leads to severe phase separation.
[0051] This invention successfully solves the Cs problem by separately controlling the temperatures of the evaporation (upstream high-temperature zone) and deposition (downstream low-temperature zone) regions, combined with the grinding treatment of the precursor powder. + With Rb + Due to ionic radius mismatch (Cs + 1.67 Å, Rb + The alloying challenges caused by the difference in volatility between the precursor and the 1.48 Å content were overcome, thus achieving high-quality, full-component two-dimensional Cs alloys. x Rb 1-xA one-step controllable preparation of PbBr3 single-crystal nanosheets was achieved. In the first step, CsBr, RbBr, and PbBr2 powders were thoroughly mechanically ground and mixed according to the target stoichiometric ratio. This process, through mechanical force, ensured highly uniform mixing of the different raw materials at the microscale, effectively increasing the reaction contact area and reducing the activation energy of subsequent gas-phase reactions. This fundamentally eliminated potential fluctuations in gas-phase composition caused by inhomogeneous initial states of the raw materials and the different volatilization rates of CsBr and RbBr, laying a solid foundation for subsequent atomically uniform alloying. In the second step of chemical vapor deposition, the gas-phase mass transfer efficiency and reaction residence time were determined by controlling the transport distance, a specific low system pressure (10-30 Torr), and the carrier gas flow rate. In particular, the low-pressure environment not only synergistically controlled the saturated vapor pressure of the precursor with temperature parameters, but more importantly, it significantly reduced the transport differentiation of Rb and Cs vapors due to differences in mass and volatility, providing an indispensable kinetic environment for achieving atomically uniform alloying. This effectively suppresses phase separation caused by lattice stress, guides the crystal to grow epitaxially in a two-dimensional layered mode, and ultimately forms a single-crystal nanosheet with pure phase and perfect crystallization.
Claims
1. A two-dimensional Cs x Rb 1-x A method for preparing PbBr3 single-crystal nanosheets, characterized by including: The following steps are required: (1) According to the chemical formula Cs x Rb 1-x Weigh CsBr, RbBr, and PbBr2 powders according to the stoichiometric ratio of each element in PbBr3, mix them thoroughly, and grind them to obtain precursor powder; where 0 ≤ x ≤ 1; (2) Place the precursor powder in a ceramic boat and place the ceramic boat in the upstream high-temperature zone of the tube furnace, and place the substrate in the downstream low-temperature zone of the tube furnace. (3) Under negative pressure conditions, the temperatures of the upstream high-temperature zone and the downstream low-temperature zone in the tube furnace are controlled so that the precursor powder in the ceramic boat in the upstream high-temperature zone evaporates and is carried by the carrier gas to the downstream low-temperature zone, thereby realizing the deposition of two-dimensional Cs on the substrate. x Rb 1-x PbBr3 single-crystal nanosheets.
2. The two-dimensional Cs according to claim 1 x Rb 1-x The method for preparing PbBr3 single-crystal nanosheets is characterized by, In step (3), the negative pressure condition is 10-30 Torr; the carrier gas is argon.
3. The two-dimensional Cs according to claim 1 x Rb 1-x The method for preparing PbBr3 single-crystal nanosheets is characterized by, In step (2), the distance between the substrate and the center of the upstream high-temperature zone is 1-2 cm; the carrier gas flow rate is 30-100 sccm; and the reaction time is 15-120 min.
4. The two-dimensional Cs according to claim 1 x Rb 1-x The method for preparing PbBr3 single-crystal nanosheets is characterized by, In step (3), when 0≤x≤0.5, the temperature of the upstream high-temperature zone is controlled at 350~420℃; the temperature of the downstream low-temperature zone is controlled at 215~275℃; when 0.5≤x≤1, the temperature of the upstream high-temperature zone is controlled at 420~500℃; the temperature of the downstream low-temperature zone is controlled at 275~325℃.
5. The two-dimensional Cs according to claim 4 x Rb 1-x The method for preparing PbBr3 single-crystal nanosheets is characterized by, In step (3), when 0≤x≤0.3, the temperature of the upstream high-temperature zone is controlled at 350~380℃; the temperature of the downstream low-temperature zone is controlled at 215~245℃; when 0.3≤x≤0.5, the temperature of the upstream high-temperature zone is controlled at 380~420℃; the temperature of the downstream low-temperature zone is controlled at 245~275℃; when 0.5≤x≤0.8, the temperature of the upstream high-temperature zone is controlled at 420~470℃; the temperature of the downstream low-temperature zone is controlled at 275~315℃; when 0.8≤x≤1, the temperature of the upstream high-temperature zone is controlled at 470~500℃; the temperature of the downstream low-temperature zone is controlled at 315~325℃.
6. Two-dimensional Cs prepared by the method according to any one of claims 1 to 5 x Rb 1-x PbBr3 single-crystal nanosheets.